2013
DOI: 10.1103/physrevd.88.123520
|View full text |Cite
|
Sign up to set email alerts
|

Two-point correlation function of density perturbations in a large void universe

Abstract: We study the two-point correlation function of density perturbations in a spherically symmetric void universe model which does not employ the Copernican principle. First we solve perturbation equations in the inhomogeneous universe model and obtain density fluctuations by using a method of non-linear perturbation theory which was adopted in our previous paper. From the obtained solutions, we calculate the two-point correlation function and show that it has a local anisotropy at the off-center position differen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 93 publications
1
19
0
Order By: Relevance
“…While the simplest scenario is the screening of the spin 1/2 by a single screening channel, in the last years the research on Kondo systems has been extended to systems in which in addition to the spin degeneracy, there is also degeneracy in other orbital degree of freedom, leading usually to a higher symmetry of the model, such as the SU(4) one [17,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50]. The presence of both orbital and spin degrees of freedom can trigger exotic environments for developing the Kondo physics.…”
Section: Introductionmentioning
confidence: 99%
“…While the simplest scenario is the screening of the spin 1/2 by a single screening channel, in the last years the research on Kondo systems has been extended to systems in which in addition to the spin degeneracy, there is also degeneracy in other orbital degree of freedom, leading usually to a higher symmetry of the model, such as the SU(4) one [17,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50]. The presence of both orbital and spin degrees of freedom can trigger exotic environments for developing the Kondo physics.…”
Section: Introductionmentioning
confidence: 99%
“…The region shaded by dashed lines in Fig. 6 represents the domain in which the approximation scheme adopted in our previous works [65,66] is applicable. The region shaded by solid lines in Fig.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Since the growth factor of the density contrast in the homogeneous and isotropic universe model is a function of only t, the dependence of the growth factor on µ and r ′ o in the huge void universe model can be a strong discriminator for these two models. In our previous works [65,66], we studied the linear perturbations in the huge void universe model without any distinctions between relativistic and non-relativistic perturbations, by treating the background huge void as an isotropic perturbation in the background model of the homogeneous and isotropic universe filled with dust. By contrast, the method of analysis based on the tidal approximation is applicable, even if the background void structure is highly nonlinear.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These occupations, the tunneling matrix elements (coupling to the leads) and the voltages at the four leads can be controlled independently. The system was proposed by Büsser et al [27] to control spinpolarized currents and is being subject of intense theoretical research [28,29,31,32,34,35]. Comparing experiment with numerical-renormalization-group (NRG) calculation, Keller et al found evidence of SU(4) Kondo behavior.…”
Section: Introductionmentioning
confidence: 99%